A short argument for truthmaker maximalism. (18th September 2019) - Jago, Mark
Abstract: Each truth has a truthmaker: an entity in virtue of whose existence that truth is true. So say truthmaker maximalists. Arguments for maximalism are hard to find, whereas those against are legion. Most accept that maximalism comes at a significant cost, which many judge to be too high. The scales would seem to be balanced against maximalism. Yet, as I show here, maximalism can be derived from an acceptable premise which many will pre-theoretically accept.